The Gunsmith: Showdown in Cheyenne - Book 348 - Roberts, J. R., 1951- (New York : Jove Books, 2010)
"Killings cheaper than divorce. At least thats how Cheyenne rancher Gerald Lawrence sees it. Word is, the Hunt gang is coming to rob his place. Sure would be a shame if Mrs. Lawrence got caught in the cross fire... But Lawrence has made two tactical errors. Hes hired Clint Adams to protect his ranch--and hes left him alone with his wife..."--P. [4] of cover.
Keywords: Adams, Clint (Fictitious character) -- Fiction; Robbery -- Fiction; Brigands and robbers -- Fiction; Ranchers -- Fiction; Gunfights -- Fiction; Western fiction